Pengaruh Organizational Commitment terhadap Readiness for Change pada Dosen - Muhammad Ghilman Al Ghifari; Hendro Prakoso (Bandung Conference Series: Psychology Science, 2023)
Abstract. Changes and developments are unavoidable in the continuity of theorganization today and in the future, including the field of educationalorganizations. Education in Indonesia is currently undergoing a change from theMerdeka Learning-Independent Campus (MBKM) program. This has an impact onhigher education and the members in it, one of which is the lecturer. These changesinclude academic activities, learning systems, and technology. Lecturers who areactively involved in implementing the values ​​and goals of higher education duringthe MBKM policy indicate an organizational commitment to the lecturers.Organizational commitment is said to have a relationship and influence on readinessto change, so that it can achieve the success of changes that occur in theorganization. This study aims to determine and analyze how much influenceOrganizational Commitment has on Readiness for Change on lecturers. Thisresearch method is a quantitative method included in causality with a sample size of70 lecturers from the Islamic University of Bandung, the University of IndonesianEducation, and the University of Pasundan. This study uses the OrganizationalCommitment Questionnaire (OCQ) from Mowday et al., (1979) and the Readinessfor Change Scale from Holt et al., (2007). The results of this study based multipleregression showed that Organizational Commitment has an effect influence onReadiness for Change by 49.9% with the dimension of identification giving a largeeffect on readiness to change. Abstrak. Perubahan dan perkembangan tidak terhindarkan dalam keberlangsunganorganisasi saat ini dan di masa yang akan datang, termasuk organisasi bidangpendidikan. Pendidikan di Indonesia saat ini mengalami perubahan dari programMerdeka Belajar-Kampus Merdeka (MBKM). Hal ini berdampak pada perguruantinggi dan anggota didalamnya, salah satunya yaitu dosen. Perubahan ini meliputiaktivitas akademik, sistem pembelajaran, dan teknologi. Dosen yang terlibat aktifdalam pencapaian nilai serta tujuan perguruan tinggi ketika diterapkan kebijakanMBKM, menandakan adanya organizational commitment pada dosen.Organizational commitment dikatakan memiliki hubungan dan pengaruh terhadapReadiness for change, sehingga dapat mencapai keberhasilan perubahan yang terjadipada organisasi. Penelitian ini bertujuan untuk mengetahui dan menganalisisseberapa besar pengaruh Organizational Commitment terhadap Readiness forChange pada dosen. Metode penelitian ini adalah metode kuantitatif termasukdalam kausalitas dengan jumlah sampel subjek yaitu 70 dosen yang berasal dariUniversitas Islam Bandung, Universitas Pendidikan Indonesia, dan UniversitasPasundan. Penelitian ini menggunakan alat ukur Organizational CommitmentQuestionaire (OCQ) dari Mowday et al., (1979) dan Readiness for Change Scaledari Holt et al., (2007). Berdasarkan hasil regresi berganda didapatkan hasil bahwaOrganizational Commitment memberikan pengaruh yang besar terhadap Readinessfor Change sebesar 49,9% dengan dimensi identifikasi yang memberikan pengaruhpaling besar terhadap Readiness for change.